Evaluation of non-carcinogenic health risks of thallium in grapevine exposed to mine waters of an abandoned mining region in Turkey - Topal, Murat; Arslan Topal, E. Isil; Obek, Erdal (Springer, 2021)
In this study, non-carcinogenic health risks of thallium in grapevine exposed to mine waters of an abandoned mining region in Turkey were evaluated. The values of thallium were investigated in leaves, stems, and roots. Translocation factors (TF) and bioaccumulation concentration factors (BCF) were determined. The maximum thallium value in grapevines (root) was 2.34 +/- 0.12 mg/kg. Thallium values in grapevine were stem < leaf < root. The bioconcentration value calculated in our study is higher than 1 showing thallium bioaccumulation from the mine water to grapevines. Translocation factor value is calculated as 1.20. The high total estimated daily exposure dose (TED) in grapevines was determined as 1.10E-02 mg/kg day for children. TEDs values in grapevines were observed as male < female < children, respectively. The maximum HQ risk value for male was observed as 1060 for children. The non-carcinogenic risk values were children > female > male. Hazard index values of thallium in grapevines were ingestion < dietary. As a result, hazard and total hazard index values were > 1 for thallium in grapevines. Therefore, there are non-carcinogenic health risks of thallium in grapevine exposed to mine waters of an abandoned mining region.
Keywords: Thallium; Non-carcinogenic; Mine water; Grapevine; Health risk